MODELLING AND OPTIMIZATION OF PERFORMANCE CHARACTERISTICS IN ELECTRICAL DISCHARGE MACHINING ON TITANIUM ALLOY (Journal of Mechanical Engineering, 2013)
Electrical discharge machining (EDM) technique possesses noticeable advantages over othermachining process and can machine any hard material effectively. Proper selection of parameters in EDM isvery much essential to achieve better performance characteristics that are still challenging. This study attemptsto investigate the effects of parameters on EDM performance characteristics on Ti-6Al-4V utilizing coppertungsten as electrode and negative polarity of the electrode. Mathematical model associating the influences ofthese variables and the EDM characteristics such as material removal rate (MRR) and tool wear rate (TWR)are set up in this study. The optimal machining conditioning in favor of MRR and TWR are estimated. Design ofexperiments method and response surface methodology techniques are adopted to attain the objectives. Analysisof variance (ANOVA) has been performed for the validity test of the fit and adequacy of the proposed models.Optimum MRR is found at high discharge ampere, long pulse on time and short pulse off time. 8A peak current,10 ?s pulse on time and 184 ?s pulse interval yields lowest TWR. The result of this investigation guides torequired process outputs and economical industrial machining optimizing the input factors.DOI: http://dx.doi.org/10.3329/jme.v43i1.15778